Heroin addiction: the past and future - Robson, Noor Zurani; Hussain, H.; Rusdi, A.R.; Muhammad Muhsin, A.Z. (Malaysian Psychiatric Association, 2008)
Substance misuse, in particular heroin addiction contributes to health and social problems. Although effective medical treatment was available, earlier efforts confined the treatment of heroin addicts to in-house rehabilitation which required them to be estranged from the community and their families for 2 years. The in-house rehabilitative programme, implemented for at least three decades has produced low abstinence rates. On the other hand, being ‘away’ meant that many heroin addicts faced employment problems and family relationship difficulties upon completing the in-house rehabilitation. However, recently, the concerted efforts by various government and non-government organisations, and the acknowledgement that heroin addiction is a medical illness has resulted in a revamp to approaching treatment of heroin addiction. At present, methadone substitution programmes have been offered as part of treatment programme for heroin addicts in Malaysia. This new programme has been shown to be effective in treating heroin addiction and would need support and cooperation from all groups involved.